Flood policy in Spain: a review for the period 1983-2013. Issue 1 (1st February 2016) - Olcina, Jorge; Sauri, David; Hernández, Maria; Ribas, Anna
Abstract : Purpose: – The purpose of this paper is to assess the main changes regarding flood policy in Spain during the period 1983-2013, that is right after the large and very damaging episodes of 1982-1983 in Valencia, Catalonia and the Basque Country. Design/methodology/approach: – This is above all a review paper that looks retrospectively at flood policy in Spain during the past three decades. In order to collect and organize the information the authors follow the methodology of the IPCC regarding vulnerability studies. That is, the authors provide evidence for an overall assessment of the evolution of exposure, sensibility and adaptive capacity to floods in Spain for the period of reference. The authors approach these issues through the own experience and expertise on this subject as noted in the reference list. Findings: – While exposure to floods has generally increased (especially after the massive growth of urbanization in flood prone land of the 1990s and early 2000s) overall flood policy has contributed to make Spain less sensible and more adapted to floods. Still some issues remain unsolved especially the control of urban growth and the adaptation of the built environment to floods. For these reasons absolute economic losses from floods may continue to be important in the future (perhaps more so with climate change) even though, overall, Spanish society may have become less vulnerable and therefore more resilient than in the past. Originality/value: – The paper provides a retrospective study and assessment of policies taken and their changes regarding floods at a national level over a long period of time (30 years) which is a theme still relatively little explored in the scientific literature on this hazard.